Contestation of Power at the Local Level: Conflict between Kerapatan Adat Nagari and the Nagari Government in Sialang - Sukri, Mhd Alfahjri; Fadri, Zainal (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the dynamics of conflict between the Nagari government and the Kerapatan Adat Nagari (KAN) in Nagari Sialang, identify its causes, assess its impact on Nagari Sialang, and propose a conflict resolution model between the two institutions. This research employs a qualitative approach with a case study design. Primary data were obtained through in-depth interviews, observations, and documentation. This study utilizes Max Weber’s theory of legitimacy to analyze the root causes of the conflict and applies the Hybrid Political Orders (HPO) framework as a conflict resolution strategy. The findings reveal that the conflict stems from differing perceptions of legitimacy. The Nagari government derives its authority from legal-formal sources, while KAN is rooted in traditional authority. Power contestation becomes more pronounced in the governance of the nagari, particularly in disputes over financial reporting of Nagari’s Own Revenue (Pendapatan Asli Nagari/PAN), KAN’s request to manage budgets outside regulatory frameworks, and authority over marriage registration documents. These tensions illustrate the struggle between modern governance and customary institutions, negatively impacting the Nagari government. This study proposes the implementation of the Hybrid Political Orders (HPO) model to integrate modern governance with customary systems in Nagari Sialang, fostering inclusive governance. The findings offer valuable insights for policymakers in resolving and preventing conflicts in nagari, or village, settings that retain traditional governance structures.